REVIEW OF PRESCRIBER APPROACH TOWARDS RATIONAL DRUG PRACTICE IN HOSPITALISED PATIENTS - Amin, Adnan; Khan, Muhammad Ayaz; Azam, Sheikh Muhammad Farooq; Haroon, Uzma (Journal of Ayub Medical College Abbottabad, 2011)
Background: The rational drug prescribing practice is an important health concern around the globe that not only interferes patient's life but also the socioeconomic issues. Objective: The aim of current study was to evaluate the rational use of drug, prescribing behaviour of consultant physicians, role of medical team members in irrational therapy and form the basis for providing necessary information to the policy makers. Methods: This cross-sectional study was conducted involving a set of 340 medication orders containing about 1,755 medications prescribed to patients in DHQ Teaching Hospital DI Khan, Pakistan from March to July 2009. The WHO operational package for monitoring and assessing country pharmaceutical situations indicators were used for data collection. Results: Among drugs prescribed per average encounter, 75% were dispensed from hospital pharmacy. Generally about 22.3% encounters of overdosing, 16.16% drug duplication, 24.25% drugdrug interactions, 3.5% adverse drug effects and 3.8% cases of contraindications were recorded. The proportion of consultations with antibiotics and injectables prescribed was 80% and 57% respectively. Likewise not less than 70% patients were prescribed NSAIDS, 67% steroids, 55% vitamin supplements, and 34% oral re-hydration solutions. Minimum 5 drugs per prescription were recorded and 70% of prescriptions were reported with high cost of therapy. Conclusion: The drug practice among hospitalised patients was clearly irrational accompanied by high levels of medication error. An accurate prescribing decision, appropriate treatment, and rational use of drugs are major needs of the day to ensure safe medication practice. Keywords: Rational drug use, adverse drug effects, generic drugs, medication profile